(untitled) (Nexus International Journal of Science and Education, 2024)
The delve to explore the influence of ego identity on the students’ willingness to acquire knowledge. In this study, the researcher selected 145 Grade 7-10 students in Jose Abad Santos II in Davao Occidental as the respondents of the study. A stratified random sampling technique was utilized in the selection of the respondents. Non-experimental quantitative research design using a descriptive-correlational method was employed. The data collected were subjected to the following statistical tools: Mean, Pearson Moment Product Correlation, and multiple linear regression analysis. Findings revealed that ego identity and students’ willingness to acquire knowledge in Jose Abad Santos II, Davao Occidental were described as extensive. Further, correlation analysis demonstrated that there is a significant relationship between ego identity and students’ willingness to acquire knowledge in Jose Abad Santos II, Davao Occidental were described as extensive. Evidently, regression analysis proved that ego identity in terms of identity achievement and identity moratorium significantly influenced the students’ willingness to acquire knowledge in Jose Abad Santos II, Davao Occidental. The researcher recommends that DepEd should also advocate for inclusive and diverse curricula that reflect the cultural, social, and intellectual diversity of students. The study, therefore, conducted for further utilization of findings through publication in reputable research journal.